Singapore SPICE: sedation practices in intensive care evaluation in Singapore – a prospective cohort study of the public healthcare system - Ng, Shin Yi (Singapore Med J, 2020)
INTRODUCTION: A study was conducted to describe the sedation practices of intensive care units (ICUs) in Singapore in terms of drug use, sedation depth and the incidence of delirium in both early (< 48 hours) and late (> 48 hours) periods of ICU admission. METHODS: A prospective multicentre cohort study was conducted on patients who were expected to be sedated and ventilated for over 24 hours in seven ICUs (surgical ICU, n = 4; medical ICU, n = 3) of four major public hospitals in Singapore. Patients were followed up to 28 days or until ICU discharge, with four-hourly sedation monitoring and daily delirium assessment by trained nurses. The Richmond Agitation and Sedation Scale (RASS) and Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) were used. RESULTS: We enrolled 198 patients over a five-month period. The mean Acute Physiology and Chronic Health Evaluation (APACHE) II score was 25.3 ± 9.2, and 90.9% were emergency hospital admissions. Patients were followed up for 1,417 ICU patient days, of which 396 days were in the early period and 1,021 days were in the late period. 7,354 RASS assessments were performed. Propofol and fentanyl were the sedative agents of choice in the early and late periods, respectively. Patients were mostly in the light sedation range, especially in the late period. At least one episode of delirium was seen in 23.7% of patients. CONCLUSION: Sedation practices in Singapore ICUs are characterised by light sedation depth and low incidence of delirium, possibly due to the drugs used.